GAL3ST2 from mammary gland epithelial cells affects differentiation of 3T3-L1 preadipocytes - Guerra Liliana (2014)
IntroductionIn the mammary gland, the involution that occurs when lactation ends is an important period for cancer development. We have previously demonstrated stromal?epithelium interactions evaluating conditioned medium of adipose tissue on breast epithelial metalloproteases activity (Creydt et al., Clin Transl Oncol 15:124?131, 2013). Here, we evaluated the effects of conditioned medium of breast epithelial mammary cells on stromal cells.Materials and methodsConditioned medium from normal murine mammary gland cell line (NMuMG) and conditioned medium proteins were obtained. Then, they were evaluated on modulation of adipocyte differentiation, using 3T3-L1 cell line.ResultsWe described, for the first time, that breast epithelial mammary cells could produce the enzyme galactose 3-O-sulfotransferase 2 (GAL3ST2). Importantly, GAL3ST2 is present in NMMuMG and two human breast cancer cell lines, and it is more strongly expressed in more metastatic tumors. When 3T3-L1 preadipocyte differentiation was triggered in the presence of conditioned medium from NMuMG or GAL3ST2, triglyceride accumulation was decreased by 40 % and C/EBPβ expression by 80 % in adipocytes. In addition, the expression of FABP4 (aP2), another marker of adipocyte differentiation, was inhibited by 40 % in GAL3ST2-treated cells.ConclusionsTaken together, these results suggest that GAL3ST2 would interfere with normal differentiation of 3T3-L1 preadipocytes; raising the possibility that it may affect normal differentiation of stromal preadipocytes and be a link to tumor metastatic capacity.